Strategies to Overcome Bullying from the Perspective of Educational Philosophy - Octavia, Nur Rezki; Ismail, Ismail (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
With thousands of child bullying cases reported annually, Indonesia's education system currently faces a significant challenge related to bullying among children. The purpose of this study is to analyze the role of educational philosophy in preventing bullying in schools by fostering students' character and morality. To develop students' morality and ethics, the philosophy of education contributes to the cultivation of positive character traits. This study employs Aristotle's virtue ethics theory to emphasize the importance of fairness, empathy, courage, and self-control in curbing bullying behavior. By integrating humanistic and ethical values into education, students are expected to develop virtuous traits, enhance social awareness, and take responsibility for their choices. This research adopts a qualitative approach by conducting a literature review to gather data from relevant journal articles and books. The findings indicate that character education based on the philosophy of education can effectively reduce and prevent bullying in schools. It also contributes to creating a safer and more secure learning environment for all students.